The Effects of the Contact Activation System on Hemorrhage - Simão, Fabrício; Feener, Edward P. (Frontiers in Medicine, 2017)
The contact activation system exerts effects on coagulation via multiple mechanisms, which modulate both the intrinsic and extrinsic coagulation cascades as well as fibrinolysis and platelet activation. While the effects of the contact activation system on blood coagulation measured as activated partial thromboplastin time shortening are well documented, genetic mutations that result in deficiencies in the expression of either plasma prekallikrein (PPK) or factor XII (FXII) are not associated with spontaneous bleeding or increased bleeding risk during surgery. Deficiencies in these proteins are often undiagnosed for decades and detected later in life during routine coagulation assays without an apparent clinical phenotype. Increased interest in the contact activation system as a potentially safe target for anti-thrombotic therapies has emerged, in large part, from studies on animal models with provoked thrombosis, which have shown that deficiencies in PPK or FXII can reduce thrombus formation without increasing bleeding. Gene targeting and pharmacological studies in healthy animals have confirmed that PPK and FXII blockade does not cause coagulopathies. These findings support the conclusion that contact activation system is not required for hemostasis. However, while deficiencies in FXII and PPK do not significantly affect bleeding associated with peripheral wounds, recent reports have demonstrated that these proteins can promote hemorrhage in the retina and brain. Intravitreal injection of plasma kallikrein (PKal) induces retinal microvascular hemorrhages and intracerebral injection of PKal increases intracranial bleeding. PPK deficiency and PKal inhibition ameliorates hematoma formation following cerebrovascular injury in diabetic animals. Moreover, both PPK and FXII deficiency are protective against intracerebral hemorrhage caused by tissue plasminogen activator (tPA)-mediated thrombolytic therapy in mice with thrombotic middle cerebral artery occlusion. Thus, while the contact activation system is not required for hemostasis, its inhibition may provide an opportunity to reduce hemorrhage in the retina and brain. Characterization of the mechanisms and potential clinical implications associated with the effects of the contact activation system on hemorrhage requires further consideration of the effects of PPK and FXII on hemorrhage beyond their putative effects on coagulation cascades. Here we review the experimental and clinical evidence on the effects of the contact activation system on bleeding and